COGNITIVE CHALLENGES IN TRANSLATING LAWS: RUSSIAN EXPERIENCE - Stepanova, Valentina; Udina, Natalia (International Journal of Psychosocial Rehabilitation, 2020)
Globalizing processes put legal aspects of economic, governmental, cultural, educational and other types of cooperation at the forefront of everyday activities; thus, the issues of quality translation of national laws are in the focus of academic studies. The article looks at difficulties arising from non-linguistic and linguistic properties of the Civil Code of the Russian Federation in terms of its translation into English. Under the focus are the translations by recognized specialists in civil and comparative laws, representing American law schools. Cognitive challenges they faced are linked with legal concepts that are differently interpreted in the continental European Civil laws, Anglo-American common law and in the Russian Civil Code. Critical analysis of certain terminology is suggested as an attempt ‘to strike a trade-off’ between the authentic Russian concept/meaning and the concept/meaning understandable to the target reader. Contrastive and contextual analysis along with the elements of statistical analysis contribute to reaching this aim. The findings of the research can be of practical implementation to those involved in legal translation or academic studies in comparative law.